Social dynamics : a senior high school worktext on understanding culture, society, and politics. - Arthur S. Abulencia (Quezon City : Brilliant Creations Publishing, Inc., 2022)
"The worktext offers features that will help learners optimize their learning experience. The multidisciplinary and interdisciplinary approaches have been employed in the discussion of the various discipline of social science, such as sociology, political science, anthropology and economics."
Includes glossary and bibliography.
English text.
Keywords: Sociology; Anthropology